OP0189 Tumor necrosis factor inhibitor treatment reduces spinal radiographic progression in ankylosing spondylitis by decreasing disease activity: a longitudinal analysis in a large prospective cohort. (15th June 2017) - Molnar, C; Scherer, A; Baraliakos, X; Hooge, M de; Micheroli, R; Exer, P; Kissling, R; Tamborrini, G; Wildi, L; Nissen, M; Zufferey, P; Bernhard, J; et al.
Abstract : Background: Whether tumor necrosis factor inhibitors (TNFi) have an influence on radiographic progression in ankylosing spondylitis (AS) remains controversial. Objectives: To investigate the impact of TNFi use on spinal radiographic progression in AS. Methods: Patients fulfilling the modified NY Criteria for AS (as assessed by central reading) in the Swiss Clinical Quality Management Cohort with at least 2 years of clinical and radiographic follow-up were included. Spinal X-rays were taken every 2 years and scored independently by 2 blinded readers according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) in chronological time order. Average score of the readers was used. Radiographic progression was defined as an increase by ≥2 mSASSS units over 2 years. The relationship between TNFi use before a 2 year X-ray interval and progression within the interval was investigated using binomial generalized estimating equation models with adjustment for potential confounding and multiple imputation of missing covariate data. Ankylosing Spondylitis Disease Activity Score (ASDAS) was regarded as a potential intermediate variable mediating the effect of TNFi on radiographic progression. It was added to the model as a time-varying variable in a sensitivity analysis. Results: A total of 420 patients with AS contributed to data for 597 x-ray intervals in adjusted analyses (1–5 intervals per patient); BL characteristics: male sex 66%, HLA-B27 81%, mean (SD) age 40.4 (10.9) years, disease duration 13.9 (9.8) years, mSASSS 6.4 (12.4), ASDAS 2.8 (1.1)). 39% of the patients were already on TNFi at first X-ray. Mean mSASSS progression in 2 years was 0.9 (2.7) units. The multivariable model (Table) shows that prior use of TNFi reduced the odds of progression in the next 2 year interval by 49% (odds ratio (OR) 0.51, 95% confidence interval (CI) 0.28–0.92, p=0.03). BL mSASSS and male sex also significantly affected progression. Adding ASDAS as a covariate to the model decreased the estimated effect of TNFi on progression: OR 0.65, 95% CI 0.36–1.17, p=0.15. In this model, a decrease in ASDAS by 1 unit would lower the odds for progression by 0.62 (p=0.001). Conclusions: TNFi seem to reduce radiographic progression in patients with AS and this effect is mediated, at least in part, by a decrease in disease activity. Acknowledgements: Supported by the Stiftung für Rheumaforschung and a research grant from the investigator initiated studies program of MSD. Disclosure of Interest: C. Molnar: None declared, A. Scherer: None declared, X. Baraliakos: None declared, M. de Hooge: None declared, R. Micheroli: None declared, P. Exer: None declared, R. Kissling: None declared, G. Tamborrini: None declared, L. Wildi: None declared, M. Nissen: None declared, P. Zufferey: None declared, J. Bernhard Consultant for: Merck Sharp & Dohme, Pfizer, Roche, U. Weber Consultant for: Abbvie, R. Landewé: None declared, D. van der Heijde: None declared, A. Ciurea Consultant for: Abbvie, Celgene, Eli Lilly, Janssen-Cilag, Merck Sharp & Dohme, Novartis, Pfizer, UCB